2010
DOI: 10.1016/j.jasms.2010.06.023
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency AC electrospray ionization source for mass spectrometry of biomolecules

Abstract: A novel high-frequency alternating current (AC) electrospray ionization (ESI) source has been developed for applications in mass spectrometry. The AC ESI source operates in a conical meniscus mode, analogous to the cone-jet mode of direct current (DC) electrosprays but with significant physical and mechanistic differences. In this stable conical-meniscus mode at frequencies greater than 50 kHz, the low mobility ions, which can either be cations or anions, are entrained within the liquid cone and ejected as dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 14 publications
1
42
0
Order By: Relevance
“…According to our previous study of iESI, we found that flow rate ranges of 0.2-50 μL/min was achieved using ac HV at frequency ranges of 300-4000 Hz which is lower than that of ac ESI (>50 kHz) [30] while using the same i.d. capillary as in normal ESI.…”
mentioning
confidence: 89%
“…According to our previous study of iESI, we found that flow rate ranges of 0.2-50 μL/min was achieved using ac HV at frequency ranges of 300-4000 Hz which is lower than that of ac ESI (>50 kHz) [30] while using the same i.d. capillary as in normal ESI.…”
mentioning
confidence: 89%
“…[147][148][149][150][151][152] For example, we can pack 25 nm to 100 nm oligo-functionalized Au, silica and polystyrene NPs into iontrack etched polyethylene terephthalate (PET) polymer conic nanopores, 134,135 and into conic silica nanocapillaries pulled by laser assisted drawing. 130,136,137 We have studied the NP assembly mechanism with two-dimensional nano-wedge models fabricated by focused ion beam milling.…”
Section: Polymer Nanopores and Nanopipettesmentioning
confidence: 99%
“…By applying high-resolution mass spectrometry, elemental compositions can be calculated from accurate mass measurements, with some prior understanding of the elements to be included in the calculation [8][9][10]. There have been many studies in which high-resolution mass spectrometry has been used for the analysis of petrochemicals, biofuels, and biomolecules [11][12][13][14]. However, even with high-resolution mass spectrometry, there are limits to the structural information that can be obtained.…”
Section: Introductionmentioning
confidence: 99%